Z trwogą wyczekując zmiany paradygmatu. Schyłek Nowej Muzyki - Schultz, Wolfgang-Andreas; Trzęsiok, Marcin (Res Facta Nova, 2019)
The text is the Polish translation of the article by Wolfgang-Andreas Schultz „In banger Erwartung eines Paradigmenwechsels. Die Endzeit der Neuen Musik” from the book "Avantgarde, Trauma, Spiritualität" (Schott Music, Mainz, 2015).